2012
DOI: 10.1371/journal.pone.0039554
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Curcumin on Pulmonary and Cardiovascular Effects Induced by Repeated Exposure to Diesel Exhaust Particles in Mice

Abstract: Particulate air pollution has been associated with increased risk of cardiopulmonary diseases. However, the underlying mechanisms are not fully understood. We have previously demonstrated that single dose exposure to diesel exhaust particle (DEP) causes lung inflammation and peripheral thrombotic events. Here, we exposed mice with repeated doses of DEP (15µg/animal) every 2nd day for 6 days (a total of 4 exposures), and measured several cardiopulmonary endpoints 48 h after the end of the treatments. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
70
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 55 publications
(101 reference statements)
5
70
0
1
Order By: Relevance
“…They were suspended in sterile normal saline (NaCl 0.9%) containing tween 80 (0.01%)to decrease aggregation, Control group received only normal saline with 0.01% tween 80 [8].The collected particles were less than 2.5μm in size. Transmission Electron Microscope (HR-TEM) (JEOL 3010) was used for morphological analysis and seen the presence of nano-size particles.…”
Section: Chemicalsmentioning
confidence: 99%
See 2 more Smart Citations
“…They were suspended in sterile normal saline (NaCl 0.9%) containing tween 80 (0.01%)to decrease aggregation, Control group received only normal saline with 0.01% tween 80 [8].The collected particles were less than 2.5μm in size. Transmission Electron Microscope (HR-TEM) (JEOL 3010) was used for morphological analysis and seen the presence of nano-size particles.…”
Section: Chemicalsmentioning
confidence: 99%
“…Either the DENPs suspensions or normal saline only was intratracheallyinstilled using a sterile syringe [8]. The administration was done on days 1, 3, 4 and 7.…”
Section: Animals and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…PAI-1 is the most potent endogenous inhibitor of fibrinolysis and is involved in the pathogenesis of several cardiovascular diseases. 34,35 An increase of PAI-1 has been observed following exposure to either DEP 36 or carbon nanotubes. 37 In conjunction with the fibrinolytic factor PAI-1, in the present study we measured the coagulation factor fibrinogen and found a significant increase following exposure to 50 nm SiNPs.…”
mentioning
confidence: 99%
“…PAI-1 is a potent endogenous inhibitor of fibrinolysis and has been reported to increase following exposure to DEPs, silica NPs, and carbon nanotubes. [46][47][48] It has been shown that a 4-week inhalation exposure to DECe in rats induced an increase of tissue factor, but not in PAI-1 concentration. 19 The discrepancy between the latter study showing the absence of an increase of PAI-1 …”
mentioning
confidence: 99%